Link survivability rate-based clustering for QoS maximisation in VANET. (4th June 2020) - Kalaivani, D.; Mouli, P.V.S.S.R. Chandra
A clustering technique is used in VANET to manage and stabilise topology information. Data communication in the cluster is performed by Cluster Heads (CH). The major issues involved in the clustering approaches are improper definition of cluster structure and maintenance of cluster structure in dynamic networks. To overcome these issues a link and weight-based clustering approach is developed along with Distributed Dispatching Information Table (DDIT). It is based on relative velocity of two same directional vehicles by forming a cluster with a number of nodes in VANET. The cluster head is selected based on link survival rate of the vehicles to provide the emergency message towards different vehicles in the cluster along with stored data packet information in DDIT table for fault prediction. Finally, an efficient medium access control protocol is used to provide prioritised message for avoiding spectrum shortage of emergency messages in the cluster. Comparative analysis between the proposed method and existing methods proves the effectiveness of our method with minimum transmission delay and reduced routing control overhead.